The Effect of Modified Aquaculture System on Water Quality in Cultivation of Catfish (Pangasius hypophthalmus - Irfan Zidni; Ayi Yustiati; Iskandar Iskandar; Yuli Andriani (JURNAL PERIKANAN DAN KELAUTAN, 2017)
The aim of this research was to analysis the effect of different aquaculture systems on the water quality in cultivation of catfish (Pangasius hypophthalmus). This research was conducted at Fourth Building Hatchery Faculty of Fisheries and Marine Sciences of Padjadjaran University from June to August 2017. The research was using Completely Randomized Design (CRD) with three treatments and four replications. The Treatment A were cultivation in recirculation system, treatment B cultivation on biofloc system, and treatment C cultivation in conventional system (control). The parameters of this research are absolute growth rate and water quality include temperature, acidity (pH), dissolved oxygen (DO), nitrate, ammonia and phosphate. Data were analyzed using the Fingerprint Analysis Variety and followed Duncan's Multiple Range Test at the level of 95%. The results showed that the modification of the cultivation system had an effect on the growth rate of catfish. The results showed that the highest absolute growth was in treatment B that is 5.3 gram. The most effective cultivation system in producing water quality in cultivation of catfish is the recirculation system. This can be seen from the low ammonia concentration value of 0.00268 mg/L, phosphate 0.45 mg/L and nitrate 0.31 mg/L at the end of the study.